From Planning for Rural Development to Planning for Deliberation: Reflecting the Mehr als Wohnen 4.0 Project - Schwab, Eva (Writingplace, 2023)
This article is a twofold reflection. It narrates the reflections going on during the first phase of a project within the wider context of shrinkage and pro-growth regional planning and in the course shows the little shifts in action and adjustments of attention that happened in consequence. It presents a tailored participatory approach that links the local and the regional scale and, in doing so, highlights the challenges of working within fixed geographical and regulatory boundaries as well as within established planning goals and strategies. Based on these experiences surrounding the development of a regional vision for “more than housing” in eastern upper Styria, the article offers a critical analysis on the reach of the project.